Psychometric properties of the Texas Revised Inventory of Grief (TRIG) in Peruvian university students: Propiedades psicométricas del Inventario de Duelo Revisado en estudiantes universitarios peruanos - Cassaretto, Mónica; Guillén, Henry; Velázquez, Tesania; Sánchez, Camila; de la Puente, Rafaella; Mejía, Miriam; Pease-Dreibelbis, M. Angélica (Revista de Psicopatología y Psicología Clínica, 2025)
ABSTRACT Objective: The Texas Revised Inventory of Grief (TRIG) is widely used to assess grief, although there is limited evidence regarding its factor structure and invariance. This study examined the psychometric properties of the TRIG, in its Spanish-adapted version (García-García et al., 2005), in Peruvian university students during the COVID-19 pandemic. Method: A sample of 1,433 students (Mage = 21.45, 62% female) participated in the study. Results: Using confirmatory factor analysis, it was found that the model with the best fit was that of two correlated factors, consistent with the original proposal [χ² (df) = 561.75(188), CFI = 0.995, TLI = 0.995, RMSEA = .041, SRMR = .045]. Invariance by gender and by experiences related to COVID-19 was confirmed, and internal consistency was adequate. Conclusions: These findings confirm the reliability, validity, and invariance of the TRIG, supporting its use as a valuable tool for assessing grief in student populations and in crisis contexts. RESUMEN Objetivo: The Texas Revised Inventory of Grief (TRIG) es ampliamente utilizado para evaluar el duelo, aunque existe evidencia limitada sobre su estructura factorial e invarianza. Este estudio examinó las propiedades psicométricas del TRIG, en su versión adaptada al español (García-García et al., 2005), en estudiantes universitarios peruanos durante la pandemia de COVID-19. Método: Participó en el estudio una muestra de 1.433 estudiantes (62% mujeres, edades entre 18 y 59 años, M = 21.45). Resultados: Mediante Análisis Factorial Confirmatorio, se encontró que el modelo con el mejor ajuste fue el de dos factores correlacionados, consistente con la propuesta original [χ² (df) = 561.75(188), CFI = 0.995, TLI = 0.995, RMSEA = .041, SRMR = .045]. Se confirmó la invarianza por sexo y por experiencias relacionadas con la COVID-19, y la consistencia interna fue adecuada. Conclusiones: Estos hallazgos confirman la fiabilidad, validez e invarianza del TRIG, respaldando su uso como herramienta valiosa para la evaluación del duelo en poblaciones estudiantiles y en contextos de crisis.